Retrato pictórico moderno: suas formas e significados - Golino, William (2010)
The portrait, like any image, is one form of specific ideology of the image field, irreducible, different from the ideologies of other fields, such as politics, literary, etc. Therefore, it is an image ideology, it means, a relatively coherent visual set of beliefs, values and representations, produced by the representative of the social class that commissions and uses it, inseparable from economy, politics and morals. By means of its forms, the portrait presents and represents the global interests and needs of the class, as well as, the particular interests and needs of the class sectors involved in its production, propagation and storage. The main way to explain it is through the analysis of composition, stylistic techniques, materials, dimensions and other original data, historically fixed. Hypothesis: The portrait is constituent to the social relations. Justification: To explain its historical insertion. Theoretical and methodological aspects: Analysis of the integration between artistic and non-artistic forms and contents. Objective: To demonstrate the ideological character of the portrait. Obtained results: The portrait forms determine their aesthetic and plastic meanings, integrated with other ambits of life, for instance, the modern portrait has modern forms while the classic and academic portrait has classic and academic forms